Biotech in Hong Kong: How Biologist-Entrepreneurs Pursued "Hong Kong's Bioscience Dream". Issue 3 (1st September 2016) - Luk, Christine Y. L.
Abstract : This article aims to put Hong Kong on the map of East Asia's biotech studies by identifying the major themes of biotech innovation specific to the city-state's colonial past and postcolonial present and future. I provide evidence of a concerted effort led by biologist-entrepreneurs to promote the biotech industry in postcolonial Hong Kong. Through assessing scientific literature, media representations, business strategies, and programmatic visions of key scientist-entrepreneurs in Hong Kong's biotech enterprise, I highlight how factors such as local history and geopolitical considerations shape the emerging "Hong Kong's bioscience dream." Using the recent discovery of a new recombinant anticancer drug, pegylated human recombinant arginase (BCT-100), as a case in point, I explore how biotech research and applications are marketed and interpreted in relation to Hong Kong's unique historical, political, and cultural context, thus making it distinct from other Asian Tigers. My analysis of the featured recombinant drug reveals a set of uniquely Hong Kong–centered cultural meanings attributed to biopharmaceutical research and benefits. This case reflects how genetic engineering and biotech research are configured and imagined within the context of the postcolonial Hong Kong Special Administrative Region.